Marine Distribution and Habitat Use of Atlantic Sturgeon in New York Lead to Fisheries Interactions and Bycatch. Issue 1 (24th March 2015) - Dunton, Keith J.; Jordaan, Adrian; Conover, David O.; McKown, Kim A.; Bonacci, Lisa A.; Frisk, Michael G.
Abstract: Population declines of Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus prompted initial fisheries closures and an eventual endangered or threatened species listing across the U.S. portion of their range in 2012. Atlantic Sturgeon aggregations and migration routes along the coast of Long Island overlap with commercial fishing activities that may lead to incidental take in nondirected fisheries. Thus, understanding the distribution and movement of Atlantic Sturgeon in relation to commercial fisheries can help management agencies determine impacts and develop bycatch mitigation measures. Stratified random sampling and targeted bottom trawl surveys were used to identify the temporal and spatial use of marine habitat in New York waters. The majority of survey captures were restricted to depths of less than 15 m and known aggregation areas. During the aggregation periods (May, June, September, and October) in known aggregation areas, catches were an order of magnitude higher than in other areas and months of the year. Northeast Fisheries Observer Program bycatch data from 1989 to 2013 was analyzed for the New York region and suggested that bycatch occurs within two main gear types: otter bottom trawls and sink gill nets. Trawling bycatch contained primarily subadult Atlantic Sturgeon and is highest during the Summer Flounder Paralichthys dentatus fishery in New York State waters. Trawling overlaps spatially and temporally with identified Atlantic Sturgeon aggregation areas, while bycatch in gill nets targeted adult fish farther offshore in federal waters. Bycatch in these fisheries may be a regional threat to recovery, and spatial and temporal closures, gear modifications, or other bycatch reduction techniques are suggested to protect aggregating and migrating fish. Received July 28, 2014; accepted November 4, 2014